Senior High School Students' Ability in Analyzing the Meaning of Song in English - Elfiza Putri Amelia; Delvi Wahyuni (Universitas Negeri Padang, 2021)
AbstractThis study aimed to invedtigate senor high school students’ ability in analyzing the meaing of song in English. the participant of this research were 20 students grade eleventh in SMA Pembangunan Laboratorium UNP who take the English subject as their elective subject. This study is descriptive research with qualitative approach. The result of the test given showed that the students’ ability in analyzing the meaning of song in English was in the category of poor. It was shown by the students’ difficulties in elaborating their ideas into some pargaraphs and the students’ difficulties in concluding convincing evidence in the body paragraph.